2020
DOI: 10.1021/acs.macromol.9b02158
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Cross-Linking of Catalytically Synthesized Poly(Aminonorbornenes)

Abstract: Amine-functionalized polymeric materials have a wide variety of applications; however, the preparation of these materials is often plagued by laborious, multistep synthetic routes. Herein, a modified and improved synthetic protocol utilizes the hydroaminoalkylation reaction to catalytically assemble amine-functionalized monomers on a gram scale with 100% atom economy. Combined with ring-opening metathesis polymerization (ROMP), amine-functionalized polymers with varying electronic properties have been synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 76 publications
2
29
0
Order By: Relevance
“…Recently, we reported the synthesis of secondary amine containing polymers using the tantalum-catalyzed hydroaminoalkylation of dienes and subsequent ring-opening metathesis polymerization (ROMP). , This strategy has opened a new avenue to synthesize amine-functionalized materials with tunable rheological and mechanical properties, and improved methods featuring green, easy to use, and inexpensive titanium catalysts would make these materials more accessible. With our new catalyst we reacted N -methylaniline with norbornadiene (NBD) and 1,5-cyclooctadiene (COD) neat to generate amine-containing monomers 1 (98 mg) and 2 (107 mg), respectively, suitable for subsequent ROMP (Figure a).…”
Section: Synthetic Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported the synthesis of secondary amine containing polymers using the tantalum-catalyzed hydroaminoalkylation of dienes and subsequent ring-opening metathesis polymerization (ROMP). , This strategy has opened a new avenue to synthesize amine-functionalized materials with tunable rheological and mechanical properties, and improved methods featuring green, easy to use, and inexpensive titanium catalysts would make these materials more accessible. With our new catalyst we reacted N -methylaniline with norbornadiene (NBD) and 1,5-cyclooctadiene (COD) neat to generate amine-containing monomers 1 (98 mg) and 2 (107 mg), respectively, suitable for subsequent ROMP (Figure a).…”
Section: Synthetic Applicationmentioning
confidence: 99%
“…We demonstrate the high reactivity and selectivity for the branched hydroaminoalkylation product through various transformations of unactivated and activated terminal alkenes with alkyl- and arylamines as well as an N-heterocycle. Finally, we feature a reaction procedure that avoids glovebox techniques and we demonstrate its utility in the synthesis of monomers suitable for making N-containing polymers , and the synthesis of building blocks for medicinally relevant amine small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional olefin polymerization using Ziegler–Natta/metallocene-based catalysts, compatibility between the amine-functionalized monomers and the polymerization catalyst remains a long-standing significant challenge. , Postpolymerization modification has been achieved, although these methods lack controlled functional group incorporation and require chemically harsh reaction conditions that often lead to chain scission/branching. , Acyclic diene metathesis (ADMET) is viable; however, multistep protocols including amine protection are required to obtain high-molecular-weight polymers . In recent years, Hillmyer and others have shown that ring-opening metathesis polymerization (ROMP) of prefunctionalized cyclooctene (COE) can be a powerful tool for the controlled synthesis of functionalized polymers. , To date this route with amines has required multistep monomer synthesis, and ROMP has proven incompatible with unprotected 5- or 3-aminated COE monomers. , Meanwhile, recent generations of efficient Mo , and Ru metathesis catalysts have enabled ROMP with strained amine-functionalized norbornene derivatives.…”
mentioning
confidence: 99%
“…Amine-functionalized materials are highly sought after due to their polarity, basicity, and nucleophilicity, allowing them to participate in intermolecular interactions and reactions with acids and electrophiles. The incorporation of these features in a polymer can produce active materials that respond to environmental stimuli or be modified to fabricate other functional materials. Amine-containing monomers have been polymerized, but often have relatively low molecular weights and high dispersity. Furthermore, commercially sourced polyamines are considerably more expensive than PE or PP.…”
mentioning
confidence: 99%
“…All materials were characterized by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC; Table ). As a result of the mass gained and propensity for dynamic associations through noncovalent interactions after amination, the temperature of thermal decomposition increased. This is most obvious when comparing VT300 with the AT300 derivatives where the most pronounced impact is seen with AT300-HNMeCy , having an 80 °C increase in thermal stability.…”
mentioning
confidence: 99%